2016
DOI: 10.3847/0004-637x/832/2/174
|View full text |Cite
|
Sign up to set email alerts
|

A VERY BRIGHT, VERY HOT, AND VERY LONG FLARING EVENT FROM THE M DWARF BINARY SYSTEM DG CVn

Abstract: On 2014 April 23, the Swift satellite responded to a hard X-ray transient detected by its Burst Alert Telescope, which turned out to be a stellar flare from a nearby, young M dwarf binary DGCVn. We utilize observations at X-ray, UV, optical, and radio wavelengths to infer the properties of two large flares. The X-ray spectrum of the primary outburst can be described over the 0.3-100 keV bandpass by either a single very high-temperature plasma or a nonthermal thick-target bremsstrahlung model, and we rule out … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 69 publications
1
90
0
Order By: Relevance
“…These properties put the mid-type M dwarf in the category of extremely active UV Cet-type stars. The energy released during the largest flare is similar to the event detected by Osten et al (2016) for DG CVn in the optical bandpass.…”
Section: Discussionsupporting
confidence: 61%
“…These properties put the mid-type M dwarf in the category of extremely active UV Cet-type stars. The energy released during the largest flare is similar to the event detected by Osten et al (2016) for DG CVn in the optical bandpass.…”
Section: Discussionsupporting
confidence: 61%
“…The Hγ/C4170 value is higher than in the observations but still in general agreement. Apparently, the same two-component multithread model in the decay phase of an E∼10 36 erg secondary flare event (F2; Osten et al 2016) during the DG CVn Superflare can also adequately explain the Balmer line and continuum flux properties in the decay phase (S#24) of the secondary flare events (e.g., at t 1.1 hr = in Figure 8) in the YZ CMi Megaflare. For a comparison of the continuum flux properties in the DG CVn Superflare and in the YZ CMi Megaflare, we refer the reader to Osten et al (2016).…”
Section: The Line Broadening and Flux Decrements In The Yz CMI Megaflarementioning
confidence: 87%
“…Following the analysis of the DG CVn superflare presented in Osten et al (2016), we assume X X 25 decay kernels = and X 0 hotspot = for S#24 and solve for X kernels using the flare-only, specific continuum flux centered at 4170 l = Å and 4785 l = Å observed at Earth. For S#113, we assume X X 25 decay kernels = and find that X X 2 hotspot kernels = by fitting to the Balmer jump ratio (C3615/C4170=1.5) in the observation; then we solve for X kernels using the flare-only, specific continuum flux centered at 4170 l = Å and 4785 l = Å observed at Earth.…”
Section: The Line Broadening and Flux Decrements In The Yz CMI Megaflarementioning
confidence: 99%
“…Table 1 provides comparison points for solar flares, and in Table 8 we note the GOES classification and other parameters for well-known solar and stellar flares to give context for the GJ −2 ) would make this an X2300-class flare. Osten et al (2016) found that the superflare observed from the young M dwarf binary system DG CVn was equivalent to an X600,000-class flare (60 W m −2 at 1 au, or 6000 W m −2 at 0.1 au, the approximate HZ distance). We note, however, that there is evidence that SXR-proton scaling relations should break down for such large events (>X10-class; Hudson 2007; Drake et al 2013).…”
Section: Application To Observed Flares From Gj 876mentioning
confidence: 99%